Investigation of drying kinetics of tomato slices dried by using a closed loop heat pump dryer - Coskun, Salih; Doymaz, Ibrahim; Tunckal, Cuneyt; Erdogan, Secil (SPRINGER, 2017)
In this study, tomato slices were dried at three different drying air temperatures (35, 40 and 45 degrees C) and at 1 m/s air velocities by using a closed loop heat pump dryer (HPD). To explain the drying characteristics of tomato slices, ten thin-layer drying models were applied. The drying of tomato slices at each temperature occurred in falling-rate period; no constant-rate period of drying was observed. The drying rate was significantly influenced by drying temperature. The effective moisture diffusivity varied between 8.28 x 10(-11) and 1.41 x 10(-10) m(2)/s, the activation energy was found to be 43.12 kJ/mol. Besides, at the end of drying process, the highest mean specific moisture extraction ratio and coefficient of performance of HPD system were obtained as 0.324 kg/kWh and 2.71, respectively, at the highest drying air temperature (45 degrees C).
Keywords: SIMULATION; BANANA; MODEL; Thermodynamics; Mechanics